2022
DOI: 10.3390/toxins14020150
|View full text |Cite
|
Sign up to set email alerts
|

Local Differences in the Toxin Amount and Composition of Tetrodotoxin and Related Compounds in Pufferfish (Chelonodon patoca) and Toxic Goby (Yongeichthys criniger) Juveniles

Abstract: Tetrodotoxin (TTX)-bearing fish ingest TTX from their preys through the food chain and accumulate TTX in their bodies. Although a wide variety of TTX-bearing organisms have been reported, the missing link in the TTX supply chain has not been elucidated completely. Here, we investigated the composition of TTX and 5,6,11-trideoxyTTX in juveniles of the pufferfish, Chelonodon patoca, and toxic goby, Yongeichthys criniger, using LC–MS/MS, to resolve the missing link in the TTX supply chain. The TTX concentration v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…fasciata as the source of TTX. This suggestion is supported by reports that the possession of similar major toxins in several different organisms, such as two species of ribbon worm [ 38 ], pufferfish and goby [ 39 ], suggests the presence of a common prey. TTX is thought to accumulate in higher trophic levels through the food chain starting from the TTX-producing bacteria [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 52%
“…fasciata as the source of TTX. This suggestion is supported by reports that the possession of similar major toxins in several different organisms, such as two species of ribbon worm [ 38 ], pufferfish and goby [ 39 ], suggests the presence of a common prey. TTX is thought to accumulate in higher trophic levels through the food chain starting from the TTX-producing bacteria [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 52%
“…The effect of prey toxins profiles on predator ones has already been demonstrated by several researchers. Thus, Ito et al [ 28 ] have shown that the TTX / 5,6,11-trideoxyTTX ratio in pufferfish ( Chelonodon patoca ) and toxic goby ( Yongeichthys criniger ) can result from this ratio in their presumable prey, the flatworm Planocera multitentaculata. In another study on Octopus vulgaris fed shellfish, containing another group of guanidinium toxins, paralytic shellfish toxins (PSTs), the similar PSTs prevailed as a result [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of toxicity have been observed in species of the genera Arothron, Amblyrhynchotes, Chelonodon, Dichotomyctere, Lagocephalus, and Sphoeroides [8][9][10][11][12][13]. TTX is also found in the species Yongeichthys criniger (Gobius criniger) of the order Gobiiformes [14][15][16][17].…”
Section: Actinopterygiimentioning
confidence: 99%